Insight and Oversight Function of BPK to Improve the Management of Indonesian Migrant Workers - Karunia, R. Luki; Andrianto, Nico (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
This research discusses the role of BPK through insight and oversight function to improve the management of the Indonesian Migrant Workers (PMI) program. The study was conducted using a qualitative approach by analyzing the contents of the performance audit report as well as the viewpoint/opinion of BPK regarding Indonesian migrant workers released by BPK from 2010 to 2021. Various performance audits are carried out periodically by BPK by targeting PMI recipient countries with multiple characteristics, which determine different strategies regarding the dynamics of policies in PMI recipient countries. This study concludes that BPK plays a significant role in encouraging the improvement of PMI management through various performance audit recommendations and viewpoints/opinions. These audit recommendations have carried out the insight and oversight functions related to governance and implementation of the PMI program, as well as policies that need to be improved accordingly. Traditionally seen as only conducting financial audits, performance audits conducted by BPK, primarily through insight and oversight functions, can improve government management related to the Indonesian Migrant Workers program.